2014
DOI: 10.9775/kvfd.2014.10583
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silicone Tube and Silicone Tube + Hyaluronic Acid Application on Adhesion Formation in Experimental Peri- and Epi-neurorrhaphy in A Rat Model

Abstract: Following neurorrhaphy in Wistar albino rats with experimental sciatic nerve cut, the effectiveness of solely silicone tube (ST) and ST plus hyaluronic acid application on preventing fibrosis was clinically and histopathologically examined. After a total nerve cut is created in sciatic nerve, interfascicular and epineural anastomosis was used. While only anastomosis was applied for the first group (Control Group), for the second group (ST Group) anastomosis + silicone tube and for the third group (ST + HA Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Due to their unique viscoelastic properties and good biocompatibility, unmodified and derived HAs are widely used for drug delivery, encapsulation in cell domains, and tissue regeneration [21,22]. Özaydın et al, have shown the reduction of myelin degeneration along with the increase in the axon regeneration by HA coating on silicone tubes in in vivo rat models with experimental peri and epineural neuropathy [23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique viscoelastic properties and good biocompatibility, unmodified and derived HAs are widely used for drug delivery, encapsulation in cell domains, and tissue regeneration [21,22]. Özaydın et al, have shown the reduction of myelin degeneration along with the increase in the axon regeneration by HA coating on silicone tubes in in vivo rat models with experimental peri and epineural neuropathy [23].…”
Section: Introductionmentioning
confidence: 99%
“…Neurorrhaphy, tissue adhesives, and grafting are the routine techniques of nerve anastomosis [1,2] . Neurorrhaphy is the most common choice, especially in situations where tension-free nerve endings are attached [1][2][3][4][5][6][7] . Fibrosis, adhesion neuroma and glioma formation after neurorrhaphy has a negative effect on nerve healing [1,4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Neurorrhaphy is the most common choice, especially in situations where tension-free nerve endings are attached [1][2][3][4][5][6][7] . Fibrosis, adhesion neuroma and glioma formation after neurorrhaphy has a negative effect on nerve healing [1,4,5] . Because of the negative effects of neurorrhaphy on healing, tissue adhesives have been developed as an alternative [1,2,8] and fibrin glue, which is used for neural anastomosis, reduces local inflammation and fibrosis and provides neurotropic factors [2,6,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…carpal tunel syndrome, spinal root compression, and trigeminal neuralgia due to vascular compression [8] . Few studies have investigated the molecular mechanisms of CCI and decompression [9] whereas some studies evaluated morphological changes [10][11][12] . However experimental evidence on neuropathic pain and CCI is still lacking.…”
Section: Introductionmentioning
confidence: 99%